Requiem for a Brother: Hasim and His Elegy to Numan Pasha - Züleyha Hayal (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
Köprülüzade Esad Pasha was a third-generation member of the noble Köprülü family who served during the 17th and 18th centuries and were known as the “Köprülü grand viziers” as they raised many qualified statesmen for the Ottoman Empire. Esad Pasha lived in the last quarter of the 17th century into the 18th and he was a poet who wrote poems under the pen name Hasim and created a divan (poetic collection). In a manuscript research conducted in the Köprülü Library, an elegy that belonged to Esad Pasha and was dedicated to his older brother Grand Vizier Numan Pasha was discovered. The elegy was written by Numan Pasha’s brother and Esad Pasha (Hasim) and is an incomplete yet voluminous part of the Divan created by Esad Pasha. The public and private personalities of the Köprülüzade brothers were revealed through the research. Esad Pasha’s literary personality and his Divan were discussed, and the elegy was examined from its semantic, literary, and aesthetic aspects and was presented as a critical text though the research. The main benefits of this study are its contribution to Esad Pasha’s Divan and his biography, the latter of which is underexplored and lacks sufficient scholarly attention. The study was shaped by an interdisciplinary approach,blending historical and literary research. It offers a comprehensive look into the life, personality, and art of Esad Pasha in history and through the lens of Hasim in literature, incorporating new perspectives based on recently uncovered information.